Perbandingan Diameter Hydrocyclone untuk Menurunkan Kadar Kekeruhan dan Total Suspended Solids pada Unit Flokulasi Hydrocyclone - Pohan, Steven Albert Christian; Amalia, Aussie (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
There are several types of water treatment, namely physical, chemical and biological, with each treatment process depending on the parameters of the pollutant to be treated. Raw water treatment generally uses physico-chemical treatment, which is useful for reducing the levels of pollutants such as TSS and turbidity, usually referred to as the coagulation-flocculation process. In the flocculation process there are different types of modifications, an example of modification is hydrocyclone flocculation. The aim of this research is to obtain information regarding the use of hydrocyclone flocculation reactors in the removal of pollutant parameters such as TSS. This research has been carried out by preparing 3 types of hydrocyclone flocculation reactors with different diameters (10 cm, 15 cm and 20 cm) where tests will be carried out to see the most optimal hydrocyclone flocculation diameter in eliminating TSS and turbidity parameters in the sample water. From the results of the research carried out, the most optimum diameter for the removal of TSS parameters and also turbidity in the sample water is a 20 cm hydrocyclone flocculation reactor with an average TSS removal percentage of 77.85% and an average turbidity removal percentage of 81%. Meanwhile, hydrocyclone flocculation reactor diameters of 10 cm and 15 cm have an average removal percentage of 60% and 70% for TSS, then for turbidity it is 59.8% and 62%.